State of knowledge: Antarctic wildlife response to unmanned aerial systems - Mustafa, Osama (2019)
The personal, commercial, and scientific use of unmanned aerial systems (UAS) in Antarctica has increased dramatically in recent years. Due to the potential benefits for, and negative impacts to, sensitive Antarctic wildlife, the use of UAS (also called unmanned aerial vehicles (UAV), remotely piloted aircraft systems (RPAS) or drones) is a widely discussed topic. Accordingly, an assessment of the current state of UAS-wildlife response research and recommendations for future work is needed. This paper summarizes recent research and the expert opinion of several national Antarctic science programs in order to support Antarctic conservation policy discussions and inform forthcoming research. It encapsulates the current knowledge on the impact of UAS on Antarctic wildlife and the recommendations of the Action Group (AG) on ‘Development of a satellite-based, Antarctic-wide, remote sensing approach to monitor bird and animal populations’ of the Scientific Committee on Antarctic Research (SCAR) for the compilation of guidelines.